(untitled) (Theatrum historiae, 2018)
The article deals with the infringement of enclosure boundaries set by the Council of Trent, using the example of the Benedictine convent at St. George’s Basilica at Prague Castle (the 17th and the 18th centuries). It defines a few key moments when the exceeding of the boundaries was possible without the dispensation of a relevant ordinary officer. In the field of an active enclosure, it was mainly the participation of a St. George’s abbess in the coronations of Bohemians queens, in the case of a passive enclosure, the visits of the members of the ruling dynasty and the presence of official guests at the coronations of princessabbesses. In the case of female convents, similar runnings counter to Tridentinum conclusions do not probably have an equivalent parallel in the Czech lands, although some of them, but to a much smaller extent, can be found in the Prague Convent of the Discalced Carmelites.